A OPTIC DISC PIT MACULOPATHY IN A 13 YEARS OLD CHILD: A RARE CASE: A RARE CASE - Sandiyanto, Sandiyanto; Helvinda, Weni (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2021)
ABSTRACT Introduction: Optic disc pit is a rare congenital abnormality of the optic disc. It is generally appears in the third or fourth decade of life; however, cases of serous detachment in children have been reported. Treatment includes argon laser to the peripapillary region, macular buckling surgery, vitrectomy combined with laser and/or gas injection. Objective: To report a case with optic disc pit maculopathy in a 13 years old child. Case Illustration: A 13 years old male presented to us with complaints of blurred vision in right eye started a month ago. No history of trauma. On examination, her visual acuities were 20/50 right and 20/20 left eye. Both anterior segments were normal, with normal intraocular pressures. OCT imaging showed optic disc pit located temporally, with associated serous macular detachment in the right eye. Result: After 12 weeks observation, there is no significant change in the examination of the visual acuity, fundus examination and OCT imaging. Conclusion: Currently there is no universally accepted treatment for optic disc pit maculopathy because the pathogenesis is not yet fully understood. In pediatric cases, 3-6 months of follow-up before any surgical and invasive procedures is appropriate. Keyword: Optic disc pit maculopathy, OCT imaging, observation.